Robotic-assisted total knee replacement: pioneering precision and the future of joint reconstruction - Kholinne, Erica; Gani, Karina Sylvana; Mitchel, Mitchel (Universa Medicina, 2025)
The advent of robotic-assisted systems has revolutionized orthopedic surgery. By enhancing precision in bone registration and resection, this technology minimizes manual errors and soft tissue damage, promising more accurate implant positioning and improved postoperative outcomes. This editorial explores the technical nuances of robotic-assisted TKR, its clinical implications, and the long-term potential for transforming patient care.